2021
DOI: 10.3390/molecules26102899
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of Phosphorylated Fish Skin Collagen/Mangosteen Scaffolds as Potential Materials for Bone Tissue Regeneration

Abstract: In this study, a potential hard tissue substitute was mimicked using collagen/mangosteen porous scaffolds. Collagen was extracted from Tilapia fish skin and mangosteen from the waste peel of the respective fruit. Sodium trimetaphosphate was used for the phosphorylation of these scaffolds to improve the nucleation sites for the mineralization process. Phosphate groups were incorporated in the collagen structure as confirmed by their attenuated total reflection Fourier transform infrared (ATR-FTIR) bands. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…This lower amount is related to the high cross-linking network formed in the samples, which leads to a few binding sites to calcium phosphate. Compared to the collagen-phosphorylated samples previously prepared, 16 the amount of mineral deposited is lower. Indeed, the presence of phosphate groups in the collagen structure serves as new nucleation sites for apatite formation inside the collagen fibers, and consequently, that approach increases the calcium phosphate precipitation.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…This lower amount is related to the high cross-linking network formed in the samples, which leads to a few binding sites to calcium phosphate. Compared to the collagen-phosphorylated samples previously prepared, 16 the amount of mineral deposited is lower. Indeed, the presence of phosphate groups in the collagen structure serves as new nucleation sites for apatite formation inside the collagen fibers, and consequently, that approach increases the calcium phosphate precipitation.…”
Section: Resultsmentioning
confidence: 72%
“…Additionally, the α1/ α2 ratio measured with optical densitometry confirmed that the extracted collagen is mainly Type I. 16 2.2. Mangosteen Extraction and Characterization.…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…The nucleation and precipitation of calcium phosphate in scaffolds occur due to the ionic activity of calcium phosphate in solution and its stimulation to create favorable local conditions to allow the nucleation and growth of calcium phosphate. Indeed, calcium and phosphate ions diffuse into scaffolds and form nuclei of critical size for nucleation and further growth of calcium phosphate crystals [ 31 ]. Additionally, nucleated apatite crystals on three-dimensional scaffolds create a favorable environment for osteoconductivity.…”
Section: Resultsmentioning
confidence: 99%